Effects of additional quality attributes on consumer willingness-to-pay for food labels - Gao, Zhifeng (Kansas State University, 2007)
Contingent valuation (CV), choice experiment (CE) and experimental auction (EA) or the combinations of the three methods are often used by researchers to elicit consumer willingness to pay for food attributes (food label). The main concern about these approaches is that different quality attributes of food are assumed independent. The problem of the independence assumption of a food attribute is that one attribute can signal information about another attribute or could be a proxy of overall product quality. In addition, in surveys consumers tend to be forced to focus on the limited attribute information that are presented by researchers, whereas in the real world, consumers have various sources of food quality information. The limited attributes provided in a survey may lead respondents to allocate their budgets to those limited attributes rather than allocate their budgets to a larger number of product attributes to truly reveal their preferences. The main objective of this study is to reveal the marginal impacts of additional food quality attributes on consumer WTP for food labels. Surveys containing a series of online CEs were collected to investigate the effects of additional beef steak attributes on consumer WTP in two different US markets. Both surveys included the same four questionnaires. Two questionnaires test the effect of additional attributes when no cue attributes are provided to the respondents, while the other two questionnaires test the effect of additional attributes when cue attributes are also presented. Every questionnaire contains two CEs, with the second CE having one more attribute than the first. Random parameters logit models are estimated for each CE in the four questionnaires with survey results from both samples, resulting in 16 sets of estimations altogether. The models with the different survey samples reveal consistent results regarding changes in WTP with more attributes added to the CEs. Consumer WTP for the most important attributes in the CE decreases when the number of attributes increases from three to four, while the WTP for the most important attributes increases when the number of attribute increase from four to five. The changes in the WTP for attributes depend on their relationships with the newly added attributes to the CEs and the number of attributes in CEs.
Keywords: Willningness to Pay; Food Label; Food Attribute; Choice Experiment; Economics, Agricultural (0503)